Geometric Perfusion Deficits: A Novel OCT Angiography Biomarker for Diabetic Retinopathy Based on Oxygen Diffusion - Chen, Siyu; Moult, Eric M.; Zangwill, Linda M.; Weinreb, Robert N.; Fujimoto, James G. (American journal of ophthalmology, 2021)
To develop geometric perfusion deficits (GPD), an optical coherence tomography angiography (OCTA) biomarker based on oxygen diffusion, and to evaluate its utility in a pilot study of healthy subjects and patients with diabetic retinopathy (DR). Retrospective cross-sectional study. Commercial spectral-domain optical coherence tomography angiography (OCTA) instruments were used to acquire repeated 3 × 3-mm2 and 6 × 6-mm2 motion-corrected macular OCTA volumes. En face OCTA images corresponding to the superficial capillary plexus (SCP), deep capillary plexus (DCP), and full retinal projections were obtained using automatic segmentation. For each projection, the GPD percentage and the vessel density percentage, the control metric, were computed, and their values were compared between the normal and DR eyes. The repeated OCTA acquisitions were used to assess the test-retest repeatability of the GPD and vessel density percentages. Repeated OCTA scans of 15 normal eyes and 12 DR eyes were obtained. For all en face projections, GPD percentages were significantly higher in DR eyes than in normal eyes; vessel density percentages were significantly lower in all but 1 projection (DCP). Large GPD areas were used to identify focal perfusion deficits. Test-retest analysis showed that the GPD percentage had superior repeatability than the vessel density percentage in most cases. A strong negative correlation between the GPD percentage and the vessel density percentage was also found. Geometric perfusion deficits, an OCTA biomarker based on oxygen diffusion, provides a quantitative metric of macular microvascular remodeling with a strong physiological underpinning. The GPD percentage may serve as a useful biomarker for detecting and monitoring DR.